Athletic induced iron deficiency: new insights into the role of inflammation, cytokines and hormones - Peeling, P.; Dawson, B.; Goodman, C.; Landers, G.; Trinder, D. (European Journal of Applied Physiology, 2008)
Iron is utilised by the body for oxygen transport and energy production, and is therefore essential to athletic performance. Commonly, athletes are diagnosed as iron deficient, however, contrasting evidence exists as to the severity of deficiency and the effect on performance. Iron losses can result from a host of mechanisms during exercise such as hemolysis, hematuria, sweating and gastrointestinal bleeding. Additionally, recent research investigating the anemia of inflammation during states of chronic disease has allowed us to draw some comparisons between unhealthy populations and athletes. The acute-phase response is a well-recognised reaction to both exercise and disease. Elevated cytokine levels from such a response have been shown to increase the liver production of the hormone Hepcidin. Hepcidin up-regulation has a negative impact on the iron transport and absorption channels within the body, and may explain a potential new mechanism behind iron deficiency in athletes. This review will attempt to explore the current literature that exits in this new area of iron metabolism and exercise.